Peningkatan Kualitas Layanan Melalui Business Process Management (BPM) dan Business Process Improvement (BPI) Di Sektor Usaha Mikro, Kecil, Dan Menengah (UMKM) - Maqnin, Lailil; Jeni Susyanti (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
The Micro, Small and Medium Enterprises (MSME) sector has high resilience so that it is able to survive the economic and monetary crisis. In the midst of increasingly fierce competition in the global market, MSMEs must face significant challenges to maintain and increase their competitiveness. In an effort to overcome this problem, innovative approaches such as Business Process Modeling (PPB) and Business Process Improvement (BPI) have become the focus of attention in formulating strategies for improving service quality in the MSME sector. This study aims to explore how implementing this approach can provide significant benefits for MSMEs in improving the quality of services. The Micro, Small and Medium Enterprises (MSMEs) sector has a crucial role in the economic growth and stability of a country. The approach through business process modeling and Business Process Improvement (BPI) has been recognized as an effective strategy in improving service quality in MSMEs. Business process modeling helps MSMEs to visualize and understand their workflows clearly, while BPI aims to improve the performance of existing business processes. Improving service quality is the key for MSMEs to maintain and increase competitiveness in an increasingly tight market. Through business process modeling and BPI, MSMEs can identify and eliminate operational inefficiencies and bottlenecks. Standardization of processes also ensures consistency in service delivery.